Socialization and Workshop for Office Renovation RW 01-RW 06 in Kebon Pala Village, East Jakarta - Ulinata; Grace Putri Dianty; Susan M. Nainggolan; Edward Surya Wijaya; Situmorang Lumay Bintang (PT FORMOSA CENDEKIA GLOBAL, 2023)
The community service activity carried out by the UKI Architecture Study Program has the theme